2017
DOI: 10.1002/acm2.12122
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the shielding ability of a tungsten functional paper for diagnostic x‐rays and gamma rays

Abstract: Tungsten functional paper (TFP) is a novel paper‐based radiation‐shielding material. We measured the shielding ability of TFP against x‐rays and gamma rays. The TFP was supplied in 0.3‐mm‐thick sheets that contained 80% tungsten powder and 20% cellulose (C6H10O5) by mass. In dose measurements for x‐rays (60, 80, 100, and 120 kVp), we measured doses after through 1, 2, 3, 5, 10, and 12 TFP sheets, as well as 0.3 and 0.5 mm of lead. In lead equivalence measurements, we measured doses after through 2 and 10 TFP s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…6 However, an irradiation field shaped at the applicator has the disadvantage of a large penumbra compared with that shaped by a skin collimator. 7 In a previous study, we reported that shielding materials containing tungsten, such as tungsten functional paper (TFP) [7][8][9][10][11][12] and tungsten-containing rubber (TCR), [13][14][15] can provide sufficient radiation shielding against therapeutic electron beams and diagnostic xrays and γ-rays. In electron therapy, TCR offers the advantages of being nontoxic to the human body and being easy to shape the irradiation field.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, an irradiation field shaped at the applicator has the disadvantage of a large penumbra compared with that shaped by a skin collimator. 7 In a previous study, we reported that shielding materials containing tungsten, such as tungsten functional paper (TFP) [7][8][9][10][11][12] and tungsten-containing rubber (TCR), [13][14][15] can provide sufficient radiation shielding against therapeutic electron beams and diagnostic xrays and γ-rays. In electron therapy, TCR offers the advantages of being nontoxic to the human body and being easy to shape the irradiation field.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed tungsten-containing materials such as tungsten containing rubber [11][12][13] and tungsten functional paper [14][15][16][17][18][19], while those do not adhere well to the body surface. Real time variable shape rubber containing tungsten (STR; Hayakawa Rubber Co., Ltd. Hiroshima, Japan), which has a density of 7.3 g/cm 3 , can be manually formed to any shape by hand when warmed to approximately 60°C, and its shape maintains at body or room temperature [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The lead-based undergarments pose several issues, including the cost and the toxicity to the human body and the environment [ 10 ]. The European Union directive Restriction of the Use of Certain Hazardous Substances (in electrical and electronic equipment), prohibited the use of lead in electrical appliances after 1 July 2006.There is therefore a strong demand for lead-free product development in health-care and industrial applications [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to cut, fold and stick onto other materials. The TFP is lead-free, so is less harmful to the body than lead-containing materials and can be applied to a patient’s body surface [ 11 , 12 ]. It is also recyclable [ 10 ].…”
Section: Introductionmentioning
confidence: 99%